Roles of Self-Directed Learning and Social Networking Sites in Lifelong Learning - Salleh, Umi Kalsum Mohd; Zulnaidi, Hutkemri; Abdul Rahim, Suzieleez Syrene; Zakaria, Abd Razak; Hidayat, Riyan (Eskisehir Osmangazi University, 2019)
The present research examines the relationship between self-directed learning and SNS that may affect lifelong learning. In study, 170 of the respondents are Masters students and 140 are PhD students in Malaysia. The study follows a relational survey to investigate and measure the degree of relationship amongst self-directed learning, SNS and lifelong learning. The findings of the research corroborate that self-directed learning positively affects lifelong learning. SEM analysis indicates significant and positive influence of self-directed learning on SNS. SNS are a positive partial mediator between self-directed learning and lifelong learning. In conclusion, self-directed learning positively influences the lifelong learning of students, which is affected by SNS. This study implies that lectures should support preservice teachers to sharpen teachers' self-directed learning and social networking in lifelong learning by giving suitable learning methods and proposing a sufficient teaching and learning atmosphere. © 2019, Eskisehir Osmangazi University.